The asymptotic behaviour of threshold-based classification rules in case of three prescribed classes - Kubaychuk, Oksana (JOURNAL OF ADVANCES IN MATHEMATICS, 2016)
We consider the problem of the classification of an object from the observation after its numerical characteristic in case of three prescribed classes. We also study a problem on finding and asymptotic behaviour of threshold-based classification rules constructed from a sample from a mixture with varying concentrations.